Layer-structure-suppressed concentration quenching of Dy3+ luminescence and the realization of a single phase white light-emitting phosphor cooperated with Tm3+. Issue 15 (21st June 2022) - Xie, Feiyan; Li, Junhao; Xu, Dekang; Xu, Hualan; Liu, Shuifu; Li, Yinuan; Wen, Yuhong; Zhang, Peilan; Zhong, Shengliang
Abstract : A special layered structure helps to suppress the concentration quenching to achieve high dysprosium–thulium co-doping single-phase white light. Abstract : The trivalent dysprosium-doped yellow phosphor is an important component for realizing single-matrix white light. However, concentration quenching and thermal quenching greatly limit its application. White light phosphors, Li3 Ba2 Gd3 (WO4 )8 :Dy 3+, Tm 3+, with a stratified scheelite structure were prepared via a high-temperature solid-reaction. Calculated using the Kubelka–Munk model, the band gap of the host is 3.71 eV, which is suitable for near-ultraviolet white LEDs. The matrix is a highly disordered monoclinic crystal with a layered structure, which suppresses the concentration quenching effect of Dy 3+ and achieves a relatively high doping concentration. A small amount of Tm 3+ (3%) was co-doped with Dy 3+ to obtain standard white light, whose CIE coordinate locates at (0.3370, 0.3213). Furthermore, the thermal quenching properties of Li3 Ba2 Gd3 (WO4 )8 :12%Dy 3+, 3%Tm 3+ were investigated, and it was found that the intensity of the phosphor at 422 K maintains 82.52% of that at room temperature, and remained at 71.34% when the temperature increased to 472 K. The results indicate that the Li3 Ba2 Gd3 (WO4 )8 :Dy 3+, Tm 3+ phosphor can be a potential single-phased white-light-emitting phosphor for NUV white LEDs.